2015
DOI: 10.1002/phar.1598
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacodynamics and Pharmacokinetics of Fluticasone Furoate/Vilanterol in Healthy Chinese Subjects

Abstract: Study ObjectiveTo investigate the pharmacodynamic and pharmacokinetic profiles of fluticasone furoate (FF)/vilanterol (VI) – a fixed‐dose combination of an inhaled corticosteroid (ICS) and a long‐acting β2‐agonist for the treatment of asthma and chronic obstructive pulmonary disease – after single and repeat administration in healthy Chinese subjects.DesignDouble‐blind, placebo‐controlled, single‐site, randomized, four‐way crossover study.SettingThe Clinical Pharmacological Research Centre at Peking Union Medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
9
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 21 publications
(32 reference statements)
6
9
0
2
Order By: Relevance
“…This contrasts with findings from a previous trial of FF monotherapy (Arnuity ELLIPTA), which showed that FF was increased in Chinese patients (C max , 181 pg/mL) compared with Caucasian patients (C max , 118 pg/mL); however, the FF dose used was higher than in the current study (200–800 vs 100 µg). The C max for FF 100 µg in the present study was also higher following repeat doses (day 7) than following a single dose (day 1), similar to findings from a previous trial of FF/VI (Relvar Breo ELLIPTA) in Chinese subjects …”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…This contrasts with findings from a previous trial of FF monotherapy (Arnuity ELLIPTA), which showed that FF was increased in Chinese patients (C max , 181 pg/mL) compared with Caucasian patients (C max , 118 pg/mL); however, the FF dose used was higher than in the current study (200–800 vs 100 µg). The C max for FF 100 µg in the present study was also higher following repeat doses (day 7) than following a single dose (day 1), similar to findings from a previous trial of FF/VI (Relvar Breo ELLIPTA) in Chinese subjects …”
Section: Discussionsupporting
confidence: 90%
“…At day 1, the overall systemic exposure of FF 100 µg in this study was low (C max , 10.46 pg/mL). Previous studies of FF PK following FF/VI (100/25 µg) administration (Relvar Breo ELLIPTA) in Chinese participants demonstrated higher day 1 exposure (C max , 26.8 pg/mL) . The differences in FF exposure are unlikely to be from variations in body weight because these values were similar to those in the current study.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Pharmacodynamic, pharmacokinetic and safety data have been tested with inhaled FF/VI in several populations, including healthy Chinese and Japanese, in patients simultaneously on ketoconazole and in patients with renal and hepatic impairment 2225. Stable pharmacokinetics and pharmacodynamics and no safety concerns over the use of inhaled FF/VI were found in these studies.…”
Section: The Use Of Ff and VI In Asthmamentioning
confidence: 99%